Digital Indonesia Connectivity and Divergence. - Jurriëns, Edwin; Tapsell, Ross ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
This book places Indonesia at the forefront of the global debate about the impact of'disruptive' digital technologies. Digital technology is fast becoming the core of life, work, culture and identity. Yet, while the number of Indonesians using the internet has followed the upward global trend, some groups the poor, the elderly, women, the less well-educated, people living in remote communities are disadvantaged. This interdisciplinary collection of essays by leading researchers and scholars, as well as e-governance and e-commerce insiders, examines the impact of digitalisation on the media industry, governance, commerce, informal sector employment, education, cybercrime, terrorism, religion, artistic and cultural expression, and much more. It presents groundbreaking analysis of the impact of digitalisation in one of the worlds most diverse, geographically vast nations. In weighing arguments about the opportunities and challenges presented by digitalisation, it puts the very idea of a technological revolution into critical perspective.
Digital Indonesia: Connectivity and Divergence -- Contents -- Tables -- Figures -- Contributors -- Acknowledgments -- Glossary -- 1. Challenges and opportunities of the digital'revolution' in Indonesia -- Part 1. Connectivity -- 2. An insider's view of e-governance under Jokowi: political promise or technocratic vision? -- 3. Mobile phones: advertising, consumerism and class -- 4. The political economy of digital media -- Part 2. Divergence -- 5. Narrowing the digital divide -- 6. Laws, crackdowns and control mechanisms: digital platforms and the state -- 7. The state of cybersecurity in Indonesia -- Part 3. Identity -- 8. Digital activism in contemporary Indonesia: victims, volunteers and voices -- 9. Social media and Islamic practice: Indonesian ways of being digitally pious -- 10. Online extremism: the advent of encrypted private chat groups -- Part 4. Knowledge -- 11. Digitalising knowledge: education, libraries, archives -- 12. Digital art: hacktivism and social engagement -- Part 5. Commerce -- 13. Indonesia and the digital economy: creative destruction, opportunities and challenges -- 14. A recent history of the Indonesian e-commerce industry: an insider's account -- 15. The Go-Jek effect -- Index -- Indonesia Update Series.
Includes bibliographical references and index.
Keywords: Sociology